Analisis dan Perancangan Sistem Informasi Presensi Menggunakan Motode Agile Berbasis Website. - Vito Putra Perdhana; Muhammad Rangga Pramudya (Journal of Information Systems and Business Technology, 2025)
The advancement of information technology today causes changes to the world of technology, one example is the attendance recording system has developed to replace the manual method that has been widely used in office environments. Manual attendance systems have several disadvantages, including the possibility of data fraud, inaccurate recording, and long reporting times, which hinder administrative performance. Conversely, certain organizations may not be able to use digital systems due to a lack of human resources and infrastructure. The purpose of this research is to solve these problems by designing and developing a digital attendance application that operates via the web. Secure login, management of employee and job title information, attendance scheduling, daily attendance recording, attendance reporting, and logout are all part of the developed system. The Agile method for system development enables an iterative and collaborative approach with users through a continuous process of sprints, testing, and evaluation. In addition, system testing was conducted using the Black Box Testing method to assess the functionality of the interface. The end result of this research is expected to offer a modern alternative that is easy to use, accurate, and efficient to replace manual systems. In addition, these results are expected to increase the transparency and effectiveness of the attendance process in the work environment.